2008
DOI: 10.1002/jnr.21626
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nogo and its receptor in the optic pathway of mouse embryos

Abstract: We have investigated the localization of Nogo, an inhibitory protein acting on regenerating axons in the adult central nervous system, in the embryonic mouse retinofugal pathway during the major period of axon growth into the optic chiasm. In the retina, Nogo protein was localized on the neuroepithelial cells at E12 and at later stages (E13-E17) on radial glial cells. Colocalization studies showed expression of Nogo on vimentin-positive glia in the retina and at the optic nerve head but not on most of the TuJ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 49 publications
7
33
1
Order By: Relevance
“…However, much current data demonstrate that Nogo-A is expressed in many populations of neurons in the CNS. Our findings of the expression of Nogo-A in the RGCs in rats is consistent with previous reports that Nogo-A is expressed in the retina of embryo or neonatal animals [18,19]. Besides the inhibition of axonal regeneration or neurite outgrowth, Nogo-A plays an important role in synapse maintenance and neural survival.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, much current data demonstrate that Nogo-A is expressed in many populations of neurons in the CNS. Our findings of the expression of Nogo-A in the RGCs in rats is consistent with previous reports that Nogo-A is expressed in the retina of embryo or neonatal animals [18,19]. Besides the inhibition of axonal regeneration or neurite outgrowth, Nogo-A plays an important role in synapse maintenance and neural survival.…”
Section: Discussionsupporting
confidence: 94%
“…Nogo-A expression was increased in the cortical neurons [16] and anti-Nogo-A antibody improves functional recovery in adult rats after stroke [17]. Nogo protein was detected in the retina of mouse embryos [18] and in the neonatal rat [19]. Neuronal Nogo-A may be involved in normal cell-functioning, which separates from the post injury outgrowth-inhibitory role observed for oligodendroglial Nogo-A [15].…”
Section: Introductionmentioning
confidence: 85%
“…Although the distributions of Nogo and NgR have been reported in many previous studies, they were limited to the restricted areas or special ages [3, 4, 7-12, 16, 17, 19, 20]. For example, we previously detected NgR proteins in the neonatal rat retina [20]; in contrast, Wang et al [17] did not detect a similar expression in the retina of E13 embryos. To clarify whether Nogo was truly expressed in the neonatal rat retina, and explore the expression patterns of Nogo and NgR in other parts of the neonatal rat visual nervous system, in the present study, we confirmed that Nogo-A was Fig.…”
Section: Discussionmentioning
confidence: 49%
“…After the rat is born, its visual system is still in a period of high plasticity that relies on a number of local cues [17]. Furthermore, among these local cues, the NgR signaling was considered to serve as a necessary regulatory point on visual system plasticity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Chan SunOn and colleagues discovered a novel developmental function of Nogo, an inhibitory molecule for axon regeneration in the adult central nervous system [7], in the sorting of VT retinal axons into the ipsilateral projection [29,30]. They observed that Nogo is expressed by radial glia in the midline within the optic chiasm, and the Nogo receptor (NgR) is expressed in retinal neurites and growth cones.…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Other Proteinsmentioning
confidence: 97%